Dietary Fermentable Fiber Reduces Intestinal Barrier Defects and Inflammation in Colitic Mice. Issue 10 (7th September 2016) - Hung, Tran Van; Suzuki, Takuya
Abstract: Background: Dietary fiber (DF) and its fermentation metabolites play an important role in establishing and maintaining intestinal health. Objective: This study investigated the effects of fermentable DF, guar gum (GG), and partially hydrolyzed GG (PHGG) on the epithelial tight junction (TJ) barrier and inflammation in a murine model of dextran sodium sulfate (DSS)–induced colitis. Methods: In Expt. 1, male, 7-wk-old BALB/c mice weighing ∼21 g were fed diets with 0%, 5%, and 10% GG for 12 d and administered distilled water with 2% DSS for 7 d beginning 5 d after the start of feeding. In Expt. 2, mice were provided diets with or without 10% PHGG and GG for 13 d and administered distilled water with 2% DSS for 8 d from 5 d after the start of feeding. In Expt. 3, mice were provided diets with or without 10% PHGG and GG for 14 d without DSS administration. Colitis score, colon TJ proteins, and fecal SCFA concentrations were analyzed. Results: In Expts. 1 and 2, the clinical score in the DSS group was ∼100% greater than that in the DSS+10% GG and PHGG groups on days 12 and 13 ( P < 0.01). The DSS+10% GG and PHGG groups showed ∼110%, 60%, 120%, and 110% greater ( P < 0.05) expression of occludin and claudin 3, 4, and 7, respectively, in the colon than did the DSS group. The DSS+10% GG and PHGG groups had greater total fecal SCFA concentrations (25.1 and 12.0 mmol/L) than did the DSS group (3.3 mmol/L) on day 9 ( P < 0.01). TJ protein expression did not differ between groups in Expt. 3. Conclusion: These findings suggest that microbial metabolites of PHGG and GG, and possibly SCFAs, reduce intestinal barrier defects and inflammation in colitic mice.